Analisis Kebutuhan History Games Menggunakan Aplikasi Wordwall Pada Pembelajaran Sejarah Kelas X Di Smkn 9 Padang - Putra, Amadial Buyatma; Yefterson, Ridho Bayu (Jurusan Sejarah FIS UNP, 2024)
This research was motivated by teachers who did not use learning media in the history learning process, causing learning to become monotonous. Therefore, it is necessary to develop History Games learning media using the Wordwall application which can increase students' interest in historical material. The aims of this research are (1) to develop History Games learning media using the Wordwall Application at SMKN 9 Padang; (2) Exploring the use of History Games Using the Wordwall Application in history learning for students at SMKN 9 Padang. The methodology in this research uses Research and Development (R&D) methodology. The model used is the ADDIE model, analysis, design, development, implementation and evaluation, but this research only reaches the implementation stage. The results of research discussing needs analysis show that the problem of students' interest and enthusiasm in studying history is still lacking, because the learning process is not optimal, interactivity is low, and students do not understand history. We give this example in particular to the events of the Hindu-Buddhist kingdom period which are taken into account in the use of media, and currently still make history learning look monotonous and uninteresting, and the use of interactive learning media in learning is still lacking. Therefore, there is a need for innovative media that can increase students' interest and enthusiasm in learning in an interactive and fun way. The media used in research as a solution is History Games learning media using the Wordwall application. It includes diverse and varied games and contains historical material, which can provide clearer information and understanding of historical events. History Games learning media Using the Wordwall application which is used as a learning media is expected to provide solutions to the problems faced and increase students' interest and enthusiasm in learning history. So that learning content is created that is in accordance with the objectives of learning history